Association between ТР53, MDM2 and NQO1 gene polymorphisms and viral load among women with human papillomavirus - A.H. AlBosale; E. V. Mashkina (Вавиловский журнал генетики и селекции)
The risk of cervical cancer is caused by persistent human papillomavirus (HPV) infection. Cervical cancer is the most frequent cancer among women. Our purpose was to investigate the association between TP53 215C>G (Pro72Arg), MDM2 -410T>G, and NQO1 609C>T gene polymorphisms with a high HPV load and the influence of gene-gene interactions on prolonged HPV infection. Eighty-nine women with a high HPV viral load and 114 healthy women were involved in a case–control study. Genotyping for TP53 215C>G (Pro72Arg) and MDM2 -410T>G SNPs was carried out by allele-specific PCR and genotyping for NQO1 609C>T was performed by a TaqMan assay. Quantitative analysis of HPV DNA was performed by AmpliSens® HPV HCR screen-titer-FRT test system. Gene-gene interactions were analyzed using the multifactor dimensionality reduction (MDR) method. The study of separate SNPs of MDM2 -410T>G and NQO1 609C>T genes did not reveal any statistically significant difference in genotype and allele frequencies among women within the two groups. The frequency of the 215G (72Arg) allele and 215GG (72Arg/Arg) genotype of the TP53 gene was significantly higher in the case group than in the control group (OR = 1.74, 95 % CI = 1.10–2.73; p = 0.02 and OR = 1.97, 95 % CI = 1.13–3.46; p = 0.04, respectively). MDR analysis showed the significance of intergenic interactions of the three studied loci TP53 (rs1042522) – MDM2 (rs2279744) – NQO1 (rs1800566) for the formation of a high HPV load (OR = 3.05, 95 % CI = 1.73–5.46; p = 0.0001).